Fatigued, But Not Frail: Perceived Fatigability as a Marker of Impending Decline in Mobility-Intact Older Adults - Simonsick, Eleanor M. (J Am Geriatr Soc, 2016)
OBJECTIVES: To evaluate perceived fatigability as a predictor of meaningful functional decline in non-mobility limited older adults. DESIGN: Longitudinal analysis of data from the Baltimore Longitudinal Study of Aging (BLSA). SETTING: National Institute on Aging, Clinical Research Unit, Baltimore, Maryland PARTICIPANTS: Five hundred forty men and women aged 60 to 89 participating in the BLSA with concurrent perceived fatigability and functional assessments and follow-up functional assessment within one to three years. MEASUREMENTS: Perceived fatigability was ascertained using the Borg rating of perceived exertion (RPE) after 5 minutes of treadmill walking at 1.5 miles per hour. Functional measures included usual and fast gait speed, the Health ABC physical performance battery (HABC PPB) and reported walking ability. Reported tiredness and energy level were examined as complementary predictors. Covariates included age, age-squared, race, follow-up time and baseline function. Meaningful decline was defined as 0.05 m/s/year and 0.07 m/s/year for usual and fast gait speed, 0.12 points/year for HABC PPB and ≥ 1 point for walking ability index. RESULTS: Over a mean 2.1 years, 20 to 31% of participants declined across functional assessments. Fatigability was associated with a 13 to 19% greater likelihood of meaningful decline across all measures (P = .002 to .02) per 1 unit RPE increase. After considering tiredness and energy level separately, findings were essentially unchanged and neither was associated with gait speed or physical performance decline. In contrast, each separately predicted decline in reported walking ability independent of fatigability (P = .03 and P < .001, respectively). CONCLUSION: Routine assessment of fatigability may help identify older persons vulnerable to greater than expected functional decline.